An analysis of product wastage arising from dosing increment granularity in four modern growth hormone administration devices. (March 2015) - Pollock, Richard F; Kappelgaard, Anne-Marie; Seitz, Lisa
<x xml:space="preserve">Abstract</x> Objective: Human growth hormone (hGH) delivery systems differ in the size of the dose increments that can be set by the patient, affecting proximity to the target (i.e., prescribed) dose which can be attained. We investigated differences in dosing increment granularity in NordiFlex®, FlexPro®, NordiPen® (all multiple dose devices) and MiniQuick® (single dose) delivery systems. Methods: A simulation model was developed to project hGH dosing in pediatric patients with growth hormone deficiency, small for gestational age or Turner syndrome, calculating the nearest dose above the target dose administrable by each device in typical EU and US cohorts and projecting the excess dose (hGH wastage) over 1 year of typical use. Results: The device with the smallest dosing increment (FlexPro 5 mg; 0.025 mg dosing increment) was projected to administer doses < 1% above the target across all indications. MiniQuick (0.2 mg dosing increment) was projected to deliver between 5 and 6% above the target dose. None of the sensitivity analyses changed the conclusion that larger dosing increments result in more hGH wastage. Conclusions: In addition to increasing dosing accuracy, finer dosing increments may result in reductions in unnecessary hGH usage, which may in turn result in reductions in the cost of hGH treatment borne by the health-care payer.